2023
DOI: 10.3390/en16237800
|View full text |Cite
|
Sign up to set email alerts
|

Global Decarbonization: Current Status and What It Will Take to Achieve Net Zero by 2050

Hon Chung Lau,
Steve C. Tsai

Abstract: A review of global CO2 emissions over the last century shows that emissions from 80 economies contributed to 95% of global emissions. Among them, 55 economies were decarbonizers, where CO2 emissions had either plateaued or were declining, while 25 economies were polluters, where CO2 emissions were still increasing. In 2021, the global CO2 emissions were 37.1 Gtpa, with 56% coming from polluters and 39% from decarbonizers. If current trends continue, global CO2 emissions will reach 49.6 Gtpa by 2050, with 81% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Each of these six projects will involve mitigating over 7 Mtpa CO 2 . Given the size of CO 2 emission by the Indian steel industry, projects of this magnitude will be needed for India to achieve net zero by 2070. , Calculations by Lau and Tsai show that to meet the net zero goal by 2050, India needs to mitigate another 200 Mtpa CO 2 over and above existing efforts . These CCS projects will mitigate half of this amount.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these six projects will involve mitigating over 7 Mtpa CO 2 . Given the size of CO 2 emission by the Indian steel industry, projects of this magnitude will be needed for India to achieve net zero by 2070. , Calculations by Lau and Tsai show that to meet the net zero goal by 2050, India needs to mitigate another 200 Mtpa CO 2 over and above existing efforts . These CCS projects will mitigate half of this amount.…”
Section: Discussionmentioning
confidence: 99%
“…40 With increasing global attention to decarbonizing the steel industry, it seems likely the EU and US will soon impose a crossborder carbon tax on imported high-carbon intensity steel. 42,43 Therefore, India's steel industry will have to lower its carbon intensity to compete in the world market. In addition, promulgation of energy policies to incentivize both public and private steel companies to lower their carbon footprint will be useful.…”
Section: Economics Of Ccsmentioning
confidence: 99%
“…Our recently published research has shown that out of the top 80 emitters of the world, 25 countries have CO 2 emission that is still increasing with GDP. 34 When countries reach the high per capita GDP stage (> $25,000), they start using less CO 2 -intensive natural gas to replace coal and increase their use of REN, which emits little to no CO 2 . At this third stage of energy transition, a country's economy starts to decouple from and decreases with CO 2 emission.…”
Section: Longitudinal Study Of High Per Capita Gdp Economies (Per Cap...mentioning
confidence: 99%
“…Our recently published research has shown that of all the top 80 emitters of the world, 55 have reached this stage. 34 It should be noted that Figures 6, 8, and 10 are plotted with per capita CO 2 in a logarithmic scale and per capita GPD on a linear scale. Although the per capita CO 2 emissions of various economies in the same per capita GDP category (low, moderate, and high) follow the same pattern, they do not lie on the same curve.…”
Section: Longitudinal Study Of High Per Capita Gdp Economies (Per Cap...mentioning
confidence: 99%
See 1 more Smart Citation